Activation and cytokine profile of monocyte derived dendritic cells in leprosy: in vitro stimulation by sonicated Mycobacterium leprae induces decreased level of IL-12p70 in lepromatous leprosy - Braga, Andre Flores [UNESP]; Moretto, Daniela Ferraz; Gigliotti, Patricia [UNESP]; Peruchi, Mariela; Vilani-Moreno, Fatima Regina; Campanelli, Ana Paula; Pereira Latini, Ana Carla; Iyer, Anand; Das, Pranab Kumar; Brito de Souza, Vania Nieto (Fundaco Oswaldo Cruz, 2015)
Dendritic cells (DCs) play a pivotal role in the connection of innate and adaptive immunity of hosts to mycobacterial infection. Studies on the interaction of monocyte-derived DCs (MO-DCs) using Mycobacterium leprae in leprosy patients are rare. The present study demonstrated that the differentiation of MOs to DCs was similar in all forms of leprosy compared to normal healthy individuals. In vitro stimulation of immature MO-DCs with sonicated M. leprae induced variable degrees of DC maturation as determined by the increased expression of HLA-DR, CD40, CD80 and CD86, but not CD83, in all studied groups. The production of different cytokines by the MO-DCs appeared similar in all of the studied groups under similar conditions. However, the production of interleukin (IL)-12p70 by MO-DCs from lepromatous (LL) leprosy patients after in vitro stimulation with M. leprae was lower than tuberculoid leprosy patients and healthy individuals, even after CD40 ligation with CD40 ligand-transfected cells. The present cumulative findings suggest that the MO-DCs of LL patients are generally a weak producer of IL-12p70 despite the moderate activating properties of M. leprae. These results may explain the poor M. leprae-specific cell-mediated immunity in the LL type of leprosy.
Keywords: leprosy; dendritic cells; IL-12p70